Faster Improvement in Migraine Pain Intensity and Migraine‐Related Disability at Early Time Points with AVP‐825 (Sumatriptan Nasal Powder Delivery System) versus Oral Sumatriptan: A Comparative Randomized Clinical Trial Across Multiple Attacks from the COMPASS Study. Issue 10 (7th September 2017) - Lipton, Richard B.; McGinley, James S.; Shulman, Kenneth J.; Wirth, R.J.; Buse, Dawn C.
Abstract : Background: Fast relief of migraine pain, associated symptoms, and migraine‐related disability are priorities in the acute treatment of migraine. Efforts to improve the pharmacokinetic profiles of acute migraine treatments with the aim of providing faster relief include the development of non‐oral routes of administration. AVP‐825 (ONZETRA ® Xsail ® ) is a delivery system containing 22 mg sumatriptan powder that uses a patient's own breath to deliver medication intranasally, targeting the upper posterior nasal cavity beyond the narrow nasal valve, an area lined with vascular mucosa conducive to rapid drug absorption into the systemic circulation. While most studies comparing treatments measure differences in proportions of patients achieving a dichotomous endpoint at fixed time intervals, in this study we compare trajectories of migraine pain and disability over time for AVP‐825 versus 100 mg oral sumatriptan tablets. Methods: We used data from the COMPASS study (NCT01667679, clinicaltrials.gov ), a double‐blind, double‐dummy, active‐comparator, cross‐over study of people with a diagnosis of migraine. Participants treated up to five qualifying migraine attacks within 1 hour of onset with either AVP‐825 plus placebo tablets or 100 mg oral sumatriptan tablets plus placebo delivery system during the first of two 12‐week treatment periods, and then switched treatment sequences to treat up to five more attacks in the second treatment period. Patients recorded ordinal migraine pain intensity and migraine‐related disability before dosing (predose), and at 10, 15, 30, 45, 60, 90 and 120 minutes. Three‐level ordinal multilevel models accounted for unique data structure (repeated measures nested within attacks for each patient) and tested for treatment differences in migraine pain and migraine‐related disability through the first 2 hours of attacks post dose. Results: Among 259 study participants (mean age 40.0 years, 84.6% female, 78.4% white), there was significant between and within person variability in migraine pain intensity and migraine‐related disability. A typical individual showed significantly faster reductions in migraine pain over the first 30 minutes and migraine‐related disability over the first 45 minutes when treating with AVP‐825 compared with oral sumatriptan. Overall levels of pain and disability also favored AVP‐825 over 2 h following treatment. Model‐based odds ratios (OR) comparing AVP‐825 to oral sumatriptan ranged from 0.38 to 0.76 for pain and 0.37 to 0.65 for disability, with OR <1 indicating reduced pain/disability in the AVP‐825 condition. Conclusions: Compared with 100 mg oral sumatriptan, treatment with AVP‐825 was associated with faster reductions in migraine pain intensity and migraine‐related disability starting at 10 minutes postdose and continuing through the first 30 minutes for migraine pain intensity and the first 45 minutes for migraine‐related disability, resulting in lower overall pain intensity and disability that lasted through the first 2 h following treatment. Both migraine pain intensity and disability varied substantially both across subjects and within subjects across attacks.